EKSISTENSI INDUSTRI KERAJINAN BERBAHAN BAKU PANDAN DURI DI DESA MBATAKAPIDU KABUPATEN SUMBA TIMUR - Piry, Santi Susana; Rewa, Karolina A. (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The pandan craft industry in Mbatakapidu Village has become an integral part of the local economy and cultural preservation. This research aims to explore and document the processes, challenges, and opportunities faced by pandan craftsmen in maintaining the sustainability of this industry. Qualitative methods were used to gain an in-depth understanding of this phenomenon, with purposive sampling techniques applied to select informants who had relevant knowledge, experience, and who were willing to be interviewed. This research reveals that the pandan thorn craft industry that the thorn pandan craft industry in Mbatakapidu Village not only plays a role in improving the local economy but also in strengthening cultural identity. Craftsmen face several challenges including market competition, limited access to capital and changing consumer preferences. But they also find opportunities through design innovation and effective marketing. The results of the research show that the existence of pandan thorn is influenced by several factors, namely 1. Availability of raw materials of pandan thorn around the craftsman’s house. 2. Production costs are relatively low. 3. Using family kindergartens. 4. There is a fairly large market opportunity, especially in Sumbanese culture which requires pandan thorn crafts. Business constraints, 1. Low bargaining position of craftsmen in product marketing. 2. Low competition with product made from plastic and have more attractive patterns and motifs. 3. The production process takes quite a long time and production quantities are limited.